PENGEMBANGAN PENDIDIKAN ISLAM BERWAWASAN SEMESTA (Alternatif Jawaban Pendidikan Masa Depan) - Mulyadi Mulyadi; Erpendi Erpendi (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2018)
Islamic education must be able to develop a paradigm that focuses on the principle of universal insight.Universal insight in education includes an insight about the Godhead that will foster an ideological attitude, idealism and goal of struggles.While insights about humans will foster wisdom, togetherness, democracy, egalitarianism, and uphold of human rights.